2003
DOI: 10.1111/j.1600-0412.2004.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with l‐arginine or placebo in women with pre‐eclampsia

Abstract: Oral L-arginine supplementation did not reduce mean diastolic blood pressure after 2 days of treatment compared with placebo in pre-eclamptic patients with gestational length varying from 28 to 36 weeks. Whether L-arginine treatment could be clinically beneficial for the mother or the fetus if started earlier in the disease process than for the women in our study remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
1
33
0
3
Order By: Relevance
“…It is also suggested that it may play a significant role in fetal growth, by stimulating insulin secretion, and as a precursor for both polyamine synthesis and NO production [10]. L-arginine treatment accelerates fetal weight gain and improves biophysical profile [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that it may play a significant role in fetal growth, by stimulating insulin secretion, and as a precursor for both polyamine synthesis and NO production [10]. L-arginine treatment accelerates fetal weight gain and improves biophysical profile [11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, L-arginine supplementation to prevent preeclampsia has been tried in several studies. Oral L-arginine supplementation was investigated by our group; the intervention did not alter blood pressure in preeclampsia (32). A recent review found that evidence is still insufficient to draw reliable conclusions as to whether L-arginine can prevent preeclampsia or its complications (33).…”
Section: Discussionmentioning
confidence: 99%
“…Staff et al [91] found no significant effect of short-term oral supplementation with L -arginine on blood pressure; however, Germain et al [92] studied 17 women with bilaterally elevated uterine vascular resistance and found that dietary supplementation with 3 g/day of L -arginine starting in the 10th gestational week resulted in significantly reduced blood pressure, improved endothelium-dependent vasodilation, and no abnormal pregnancy outcome. This finding is in accordance with experimental data showing that L -arginine reduced blood pressure in pregnant rats with reduced uterine perfusion [93] .…”
Section: How Can Adma Be Quantified?mentioning
confidence: 99%